Pathogenic Intestinal Bacteria Enhance Prostate Cancer Development via Systemic Activation of Immune Cells in Mice - Poutahidis, Theofilos (Public Library of Science, 2013)
A role for microbes has been suspected in prostate cancer but difficult to confirm in human patients. We show here that a gastrointestinal (GI) tract bacterial infection is sufficient to enhance prostate intraepithelial neoplasia (PIN) and microinvasive carcinoma in a mouse model. We found that animals with a genetic predilection for dysregulation of wnt signaling, Apc (Min/+) mutant mice, were significantly susceptible to prostate cancer in an inflammation-dependent manner following infection with Helicobacter hepaticus. Further, early neoplasia observed in infected Apc (Min/+) mice was transmissible to uninfected mice by intraperitoneal injection of mesenteric lymph node (MLN) cells alone from H. hepaticus-infected mutant mice. Transmissibility of neoplasia was preventable by prior neutralization of inflammation using anti-TNF-α antibody in infected MLN donor mice. Taken together, these data confirm that systemic inflammation triggered by GI tract bacteria plays a pivotal role in tumorigenesis of the prostate gland.